Strategi Pemerintah Daerah dalam Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM): (Studi Empiris di Dinas Koperasi, Usaha Mikro Kecil dan Menengah Kabupaten Tulungagung) - Soebiantoro, Soebiantoro; Engelien Yusniar Permanasari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research holds significant urgency as Micro, Small, and Medium Enterprises (MSMEs) are key drivers of the local economy and play an important role in improving community welfare. The purpose of this study is to analyze the local government’s strategies in empowering MSMEs, to determine the effectiveness of the strategies implemented, and to identify the challenges and opportunities in MSME empowerment. This study employs a qualitative approach with a descriptive qualitative research design. Data were collected using purposive sampling through interviews, observations, and documentation. The data were then analyzed through data condensation, data display, and conclusion drawing. The results of the study show that the strategies of the Department of Cooperatives, Micro, Small, and Medium Enterprises of Tulungagung Regency in empowering the MSME sector are carried out through three main approaches: human resource empowerment strategies, supporting strategies, and institutional strategies. Human resource empowerment is implemented by fostering new entrepreneurs through entrepreneurship training. Supporting strategies are carried out by organizing MSME product exhibitions both online and offline as an effort to expand market reach. Meanwhile, institutional strategies are implemented through the formation of business groups, cooperative empowerment, and strengthening the capacity and quality of community enterprises. However, the implementation of these strategies faces several internal obstacles, including limited budgets that prevent regular training, low competence and professionalism of human resources, and a conservative mindset among the community that hinders innovation. In addition, the lack of public support and appreciation for local products also contributes to the slow development of the MSME sector in Tulungagung Regency.